Aufweichen, abbremsen, abschirmen - Barkhausen, David; Bloching, Sven; Engeler, Hannah (Zeitschrift für angewandte Linguistik, 2023)
This study examines the use of metaphors in the German debate on European monetary and fiscal policy. Though the debates in this policy area garnered considerable interest among linguists, so far there is a gap concerning interdisciplinary comparative studies that examine metaphorical expressions in regard to their divergent political use. This study addresses said gap by posing two explorative research questions: Which metaphors shape the German political debate on European monetary and fiscal policy? And is there a relationship between the use of metaphors and the political perspective of the people using them? To examine these questions, we developed an innovative methodological triangulation that combines qualitative, hermeneutic metaphorical analyses with quantitative, data-driven approaches of corpus linguistics. By analyzing the communication of eleven political actors during three debates on Eurozone policy, we identify the most salient metaphors and compare their political usage. Our results show four types of metaphorical expressions which can be distinguished by their relative openness regarding political perspective and their respective referent. Thereby, this study firstly provides an important guide to understanding the debate at hand; secondly, sharpens the theoretical underpinnings of the comprehension of political metaphors as a whole; and thirdly, is a valuable contribution to the methodical study of metaphorical expressions in the field of applied linguistics.
Gesehen am 26.03.2024